Maternal mental health and partner-delivered massage: A pilot study. Issue 3 (May 2021) - Hall, Helen; Munk, Niki; Carr, Bethany; Fogarty, Sarah; Cant, Robyn; Holton, Sara; Weller, Carolina; Lauche, Romy
Abstract: Background: Anxiety and depression affects many pregnant women. Massage may be beneficial for supporting mental wellbeing during this time. The aim of this study was to assess the feasibility and acceptability of a partner-delivered relaxation massage program for pregnant women, and its impact on symptoms of antenatal anxiety, stress and depression. Methods: A feasibility randomised controlled trial was conducted to compare partner-delivered relaxation massage (intervention) with self-directed stress management (control). Women attended an initial workshop at 28–32 weeks gestation followed by completion of a self-directed massage or stress management program. Qualitative data about the feasibility and acceptability (primary outcomes) were collected via online participant diaries and post-birth interviews. Anxiety, depression and stress symptoms (secondary outcomes) were assessed using the Depression and Anxiety Stress Scale (DASS-21). Birth outcomes were collected at the post- birth interview. Results: A total of 14 women/partner dyads in the massage group and 13 women in the self-directed stress management group, attended the initial workshops. When interviewed, participants from both groups reported that the programs were feasible and acceptable. Women's mean scores on all subscales of the DASS-21significantly decreased over time in both the intervention and the control group. Conclusion: Pregnant women found the partner-delivered massage program to be feasible and acceptable. Both programs decreased women's symptoms of anxiety, depression and stress with no significant differences identified between the two groups. An adequately powered experimental study with a large representative sample is needed to determine whether partner-delivered relaxation massage reduces pregnant women's symptoms of anxiety, depression and stress.